PENGARUH LINGKUNGAN KERJA NON FISIK, PENGHARGAAN (REWARD), DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN (STUDI PADA CV CAHAYA BUNGA KREASI BEKASI JAWA BARAT) - Badar, Imam Rachmatullah; Rahardja, Edy (Diponegoro Journal of Management, 2020)
Problems that occur in the CV. Cahaya Bunga Kreasi is an indication that the performance of staff and employees is felt to be decreased, namely a decrease in the results of employee performance appraisals of CV. Light of Flowers Creations. Previous research from Ibrar and Khan (2015) and Njanja dkk (2013) have added the managerial phenomenon with contradicted finding. The purpose of this study was to analyze the effect of non-physical work environment, reward and work motivation on employee performance of CV. Cahaya Bunga Kreasi. Population and sample were the same (77 employees), this research considered as using census approach. Data was collected using questionnaire.and then analyzed by multiple linear regression. The ressults showed that all three independent variable; non-physical work environment, reward and work motivation have a positive effect on employee performance. The model can explain 63,1 percent of the problem based on the adjusted R square score and the rest based n other external factors beside all variables used in this research.